1991
DOI: 10.1177/002199839102500302
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Cure Simulation of Thick Thermosetting Composites

Abstract: An investigation into the two-dimensional cure simulation of thick thermosetting composites is presented. Temperature and degree of cure distributions within arbitrary cross-sectional geometries are predicted as a function of the autoclave temperature history. The heat conduction equation for two-dimensional, transient anisotropic heat transfer is coupled to the cure kinetics of the thermosetting composite material. A heat generation term, expressed as a function of cure rate and the total heat of reaction, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(178 citation statements)
references
References 17 publications
5
173
0
Order By: Relevance
“…Typically, these models involve three aspects: first, the coupled solution of cure kinetics and heat transfer equations to obtain the temperature and degree of cure profiles in the part; this is especially important for thick composites [8][9][10]; second, the development of models for resin, laminate, and composite property evolution with cure and temperature; and third, the solution of the structural mechanics equations to estimate the induced strains and residual stresses in the part. Models for composite property evolution during cure can be based on direct experimental measurements on the composite itself during cure [11][12][13][14].…”
Section: Background: Simulation Of Residual Stresses At Part Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, these models involve three aspects: first, the coupled solution of cure kinetics and heat transfer equations to obtain the temperature and degree of cure profiles in the part; this is especially important for thick composites [8][9][10]; second, the development of models for resin, laminate, and composite property evolution with cure and temperature; and third, the solution of the structural mechanics equations to estimate the induced strains and residual stresses in the part. Models for composite property evolution during cure can be based on direct experimental measurements on the composite itself during cure [11][12][13][14].…”
Section: Background: Simulation Of Residual Stresses At Part Levelmentioning
confidence: 99%
“…In the subsequent, a simple implementation of the multiscale modeling framework is demonstrated in the context of a thick unidirectional continuous-glass-fiber-reinforced thermoset polyester matrix composite; this polyester system has been characterized by Bogetti and Gillespie [9,15]. The implementation of the first step of the multiscale modeling framework is described in Section 2; in this section the correlations derived by Bogetti and Gillespie [15] for calculation of the average properties of the unidirectional composite using self-consistent field micromechanics theory are summarized.…”
Section: Motivation and Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…The study of processing a thick composite laminate found a very low heating rate before gel point which can control the temperature in an allowed range. But the manufacturing time is increased by 27% [74][75][76]. Autoclave curing thick-section laminates may cause anisotropy of viscosity and degree of curing.…”
Section: Microwave Curing Of Composite Materialsmentioning
confidence: 99%